Exploring physicians’ decision making and perception of quality in health care delivery - Mikkelsen, Yngve (Cranfield University, 2013)
The importance of health and quality health care in people’s daily lives is widely recognised. Physicians play a key role in delivering quality health care and improved patient outcomes. However, the evidence regarding physicians’ decision making and their perception of quality of health care delivery and its influencers is inconclusive. The overall aim of this thesis is to increase the understanding of quality in health care delivery and the factors that influence it from a physician’s perspective. This aim is fulfilled by conducting three interlinked research projects. The first research project comprises a systematic review of the literature that identifies the factors, contexts and theoretical underpinnings influencing physician decision making. The synthesis of 160 studies reveals two main categories of influencing factors. The first is ‘Contexts’, which refers to the set of circumstances or facts surrounding a particular event or situation. The second category is ‘Interventions’, which are the techniques, processes or actions introduced to create changes in how physicians make decisions while performing their clinical duties. Although extant literature provides ample evidence on factors influencing physician decision making the link to quality in health care is under researched. In the second research project, the author explores how physicians construct quality of health care delivery by means of investigating 162 clinical cases with 27 repertory gird interviews that yield eleven key constructs representing a classification of physicians’ conception of quality. The third research project examines physicians’ perceptions of enablers and barriers to quality in health care delivery, employing semi-structured interviews. Findings indicate that physician’s effort in delivering quality health care is largely influenced by factors affecting behavioural control (freedom to act). This research makes five contributions to knowledge. First, a novel classification of factors influencing physician decision making when prescribing is developed, providing new understanding of the link between these factors and quality of health care. Second, the systematic review shows an innovative application of factor analysis to structure the findings of a complex phenomenon. Third, the study presents a new conceptualisation of physicians’ construction of quality in health care. Fourth, the research provides a categorization of physicians’ perceived enablers and barriers to quality health care and the mechanisms by which they operate. Finally, this research develops a theoretically-grounded and empirically-informed conceptual model that incorporates three hitherto separate domains: agency, planned behaviour, and decision theories. This model provides a new integrated lens to better understand the complexities influencing quality in health care delivery. This study also makes two significant contributions to practice. First, the findings have helped initiate a transformation in the pharmaceutical industry’s business model, evolving from business-to-person to business-to-business. Second, the findings serve as a catalyst to drive organizational changes at Norway’s largest emergency hospital. As a result, a national debate was initiated, involving the Prime Minister and Minister of Health, on how hospital emergency care can best be provided at a national level.
Keywords: agency; behaviour; context; control; interventions; mechanism; outcome; uncertainty